Proposition end validation of regressive mathematical models to estimate maximum dynamic force from predictive neuromuscular variables - Ney Marcos da Luz Pedroso; João Augusto Reis de Moura; João Luiz Zinn (Universidade Federal de Santa Catarina, 2002)
The purpose of this study was to propose and validate mathematical models to estimate the Maximum Dynamic Force (MDF) from predictive neuromuscular variables, and to verify if they are upheld by a statistic process of cross-validation, The sample consisted of 75 women, 18 to 30 years of age, and well acquainted with Resistance Weight Exercises (RWE). The sample was divided into two groups: group I (n=55) utilized in the statistical process for developing the proposed mathematical models, and group II (n=20) utilized for the process of validation of those models. independent variables were the neuromuscular Maximum Repetitions (MR) executed in the Frontal Pull (FP) and Knee Flexion (KF) exercises. The dependent variable was MDF measured on 10 RWE apparatus by means of the 1 MR test, according to the Moura et al. protocol (1997). Multiple Regression Analysis was used to produce proposed mathematical models, and cross-validation (Lohman, 1992), with signifi cance set at p<0.05, was used to verify their validity. Ten regressive mathematical modes were proposed based on the two predictive variables (MR), all of them highly signifi cant (p<0.0001). However, after the cross-validation process, only 4 mathematical models retained validity through the analysis of the adopted criteria. It was concluded that the predictive neuromuscular variables, in isolation, offered good predictive power for MDF, confi rming, therefore, 4 of the mathematical models. RESUMO Neste estudo buscou-se propor e validar modelos matemáticos para estimativa da Força Dinâmica Máxima (FDM) a partir de variáveis preditivas neuromusculares, e verifi car se estes são sustentados através de um processo estatístico de validação cruzada. Para tal selecionou-se uma amostra composta por 75 mulheres na faixa etária 18 a 30 anos, todas familiarizadas com Exercícios Resistidos com Pesos (ERP). A amostra foi seccionada em dois grupos: grupo I (n=55) utilizado no processo estatístico de proposição dos modelos matemáticos, e grupo II (n=20) utilizado para o processo de validação destes modelos. As variáveis independentes foram as neuromusculares Repetições Máximas (RMs) realizadas nos exercícios Puxada Frontal (PF) e Flexão de Joelhos (FJ). A variável dependente foi a FDM mensurada em 10 aparelhos de ERP através do teste de 1RM, protocolo de Moura et al. (1997). Utilizou-se da Análise de Regressão Múltipla para proposição dos modelos matemáticos, e para verifi car se estes seriam sustentados, utilizou-se o processo devalidação cruzada (Lohman, 1992) com signifi cância de p<0,05. Foram propostos 10 modelos matemáticos regressivos baseados em duas variáveis preditivas (RMs), todos altamente signifi cativos (p<0,0001). Contudo, no processo de validação cruzada somente 04 modelos matemáticos sustentaram validade através da análise dos critérios adotados. Conclui-se que as variáveis preditivas neuromusculares, isoladamente, apresentam bom poder preditivo da FDM, sustentando assim 04 modelos matemáticos a partir delas ajustadas.